2017
DOI: 10.1097/md.0000000000009291
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine as an adjunctive therapy to oral montelukast for treating patients with chronic asthma

Abstract: Background:This study aimed to explore the efficacy and safety of Ping Chuan Ke Li (PCKL) as an adjunctive therapy to oral montelukast compared with placebo plus montelukast for treating patients with chronic asthma (CAS).Methods:This randomized controlled trial involved 72 patients with CAS. They were randomly allocated to an intervention group or a control group, 36 subjects per group. Participants in the intervention group received PCKL and oral montelukast, while those in the control group received placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 15 publications
0
20
0
6
Order By: Relevance
“…The results demonstrate that as baseline FEV 1 % increased, effect sizes within the TM groups tended to decrease. In the three studies unsuitable for meta‐analysis for which baseline data were available, the results demonstrated similar effects for baseline severity …”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…The results demonstrate that as baseline FEV 1 % increased, effect sizes within the TM groups tended to decrease. In the three studies unsuitable for meta‐analysis for which baseline data were available, the results demonstrated similar effects for baseline severity …”
Section: Resultsmentioning
confidence: 75%
“…Three studies provided data using different scales (Table ). The study of mild–moderate asthma reported a significant improvement in the TM group, while another study showed no difference between groups . In the third study there was a significant baseline difference favouring the control group, therefore the EoT result may not be accurate.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations